Isolation and characterization of halotolerant aerobic bacteria from oil reservoir - Md. Illias, Rosli; Ooi, Seok Wei; Idris, Ahmad Kamal; Wan Abdul Rahman, Wan Aizan (Penerbit UTM Press, 2001)
Several halotolerant bacteria were isolated from brine samples from Semangkok oil reservoir. Biochemical and morphological characterization of the bacteria were carried out. These bacteria are gram positive spore formers and have been identified as belonging to the genus Bacillus. Most of the isolates could grow in medium containing kerosene as sole carbon source and energy and tolerate NaCl concentration up to 15%. Interfacial tension and surface tension tests showed that the bacteria were capable of producing biosurfactant. Six out of nine were able to produce exopolysaccharide. We believe these isolate could be appointed as future biopolymer producer especially for microbial enhanced oil recovery (MEOR).